CHSE-Based Tourism Village Development Strategy to Increase Tourist Trust - Supriadi, Bambang; Marcus, Ronald David; Said, Mochammad Fauzie; Ratnaningtyas, Djuwitawati (Proceedings of International Conference of Graduate School on Sustainability, 2022)
This study aims to analyze the practice of the CHSE (Cleanliness, Health, Safety, and Environment Sustainability) protocol to increase tourist trust in East Java tourism destinations; research the CHSE Information System for tourist villages to build tourist trust & satisfaction after the COVID-19 pandemic in East Java tourist destinations because East Java Province is a strategic area for developing national tourism potential contained to Master Plan for National Tourism Development, the population of the CHSE Information System Research System for tourist villages in East Java is 112 tourist villages. The results showed that the CHSE-Based Tourism Village is in quadrant one, where this CHSE-based tourist attraction has strengths and opportunities to be developed, considering that this tourism potential rests on the power of the CHSE-based tourism attraction in the form of unique cultural and natural tourism, sustainable ecology, and community empowerment. The convenience of traveling and the high tourist motivation opportunities are in the unique ecotourism attractions. Keywords: CHSE, Covid-19, Tourism Village